Fisheries, food, and health in the USA: the importance of aligning fisheries and health policies - David Clifford Love; Patricia Pinto da Silva; Julia Olson; Jillian Parry Fry; Patricia Mary Clay (Agriculture & Food Security, 2017)
Abstract Background Food availability, access, and utilization are the three pillars of food security and need to be aligned in order to support a healthy population. United States (US) fisheries policy plays an important role in seafood availability. US health policy impacts access and utilization of seafood in various ways; however, health policies are often disconnected from fisheries policy. Aligning fisheries and health policies is imperative to improve food security. We address two questions with our work: (1) how would US federal fisheries policy be different if our fisheries were managed with beneficial health outcomes for Americans as clear objectives; and (2) how would US health policy be different if one of its goals was to support sustainable domestic fisheries and aquaculture? Results We report how fisheries policies and health policies are additive, synergistic, or antagonistic with regard to seafood, and provide illustrative examples of collaboration between health and fisheries communities at different levels of the food system (federal and state policies, corporate partnerships, and civil society). We also develop a list of topics for future research, and opportunities to align and integrate fisheries and health policies. Conclusions Managing fisheries to promote optimal nutrition and efficient food production likely requires a different approach to fisheries management—new outcomes will need to be monitored, new approaches found, and fisheries, aquaculture, and health policies better integrated. Health policies rarely consider the source of fish, their connections with US fisheries systems, and global distribution of seafood. Change can begin where the most promising opportunities exist, such as institutional food procurement, Farm to School programs, social marketing campaigns, and private sector start-ups. Continued development in fisheries and health policies, however, will need to occur at multiple levels of federal policy, and across the different domains and dimensions of the food system (e.g., social, political, biophysical, economic).